Specific Features of Police Care Regarding the Minors - S. V. Medvedenko; M. V. Zaburannyi (Bulletin of Kharkiv National University of Internal Affairs)
The article is focused on the problems of legal regulation of preventive police action – police care. The authors have carried out the analysis of scientific works, the authors of which studied the peculiarities of the procedure of police care in regard to minors. The newly introduced legal institution of “police care” has been characterized; the legal status of a child has been determined. The authors have established the qualities of a police officer to effectively ensure the rights and interests of children. The authors have provided the relevant recommendations for improving the regulation of legal relations in the field of police care regarding the minors.